Women empowerment and childhood stunting: evidence from rural northwest Ethiopia - Emebet Gashaw Wassie; Mesfin Wogayehu Tenagashaw; Tenaw Yimer Tiruye (BMC, 2024)
Abstract Background Women are often the primary caregivers of children, and as such, their empowerment could influence the nutritional status of their children. However, the role of maternal empowerment on the nutritional status of children in Ethiopia is largely unknown. Aim To determine the association of women's empowerment with childhood stunting in rural northwest Ethiopia. Methods A community-based cross-sectional study was conducted among 582 mothers with children aged 6-59 months. A multistage sampling technique was used to select the study participants. Binomial logistic regression analyses were used to assess whether women's empowerment (categorized as low, moderate and high) and its five dimensions (household decision-making, educational status, cash earnings, house/land ownership, and membership in community groups) were associated with stunting in children. Odds ratios with 95% CI were estimated, and statistical significance was declared at a p-value of < 0.05. Results A total of 114 (19.6%), 312 (53.6%), and 156 (26.8%) participants had low, moderate, and high empowerment levels, respectively. In addition, 255 (43.8%) mothers had children who were stunted (too short for their age). In the adjusted models, mothers with moderate empowerment (AOR 0.60, 95% CI: 0.35, 0.97) and high empowerment (AOR 0.56, 95% CI: 0.37, 0.86) had lower odds of having stunted children compared to mothers with low empowerment. Mothers who had a secondary education or higher (AOR 0.57, 95% CI: 0.35, 0.93), owned a house or land (AOR 0.64, 95% CI: 0.44, 0.94) and were members of community groups (AOR 0.54, 95% CI: 0.36, 0.80) were less likely to have stunted children. Conclusion High women empowerment was significantly associated with a lower likelihood of childhood stunting. The findings suggest a need to look beyond the direct causes of stunting and incorporate targeted strategies for empowering women into child nutrition programs.